Analysis Effects of Using Type of Advertisement In Instagram towards Brand Awareness and Purchase Intention on Food Industry - Andri Ronaza, Muhammad; Wisesa, Anggara (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. The growth of the food industry in Indonesia is increasing, leading to competition among companies in the food industry. Companies need to do promotion in order to survive in existing competition. One place to do promotion is to use advertising in social media (Instagram). Based on the results of preliminary research there are three advertisements on Instagram that influence the awareness of a brand and brand awareness make costumer want to buy a brand or product that is paid promote, celebrity endorsement, and Instagram ads. Where these three ads are still not much studied in the food industry and will help companies in understanding the relationship occurs. This research uses a quantitative approach with 166 respondents. The data will be obtained by using multiple linear analysis and simple linear analysis. The results of data processing showed that the three advertisement on Instagram affected brand awareness simultaneously and also separately, where celebrity endorsement had the most influence on brand awareness followed by paid promote and Instagram ads. And brand awareness has a significant influence on the purchase intention but still many factors that affect the purchase intention in addition to brand awareness. Companies can use advertisements to increase brand awareness starting with celebrity endorsements and followed by two others. And brand awareness created can increase customer purchase intention.Â Keyword: Advertisement, brand awareness, purchase intention